Račun brez Korošca? - Rahten, Andrej (Studia Historica Slovenica, 2018)
On the basis of archival and memoir sources, the author describes the views of Anton Korošec's leading Slovenian policy on state issues in the time of the Kingdom of Yugoslavia. Korošec's views on the establishment of the Banovina of Croatia in 1939 and, consequently, the dilemmas surrounding the further decentralization of the Yugoslav state, including the possibilities for establishing a similar Slovenian state entity, are evaluated in this context. The author notes that the Banovina of Slovenia remained an unfulflled demand for Slovenian politics. The combination of military events, foreign political turbulence, and nationalistic frictions in internal politics precluded the further reorganization of the country
Keywords: Hrvaška; Jugoslavija; Korošec, Anton; Kraljevina SHS; Slovenija; zgodovina